An Eco-Friendly Hydrophobic Deep Eutectic Solvent-Based Dispersive Liquid–Liquid Microextraction for the Determination of Neonicotinoid Insecticide Residues in Water, Soil and Egg Yolk Samples - Rawikan Kachangoon; Jitlada Vichapong; Yanawath Santaladchaiyakit; Rodjana Burakham; Supalax Srijaranai (Molecules, 2020)
A green, simple and sensitive hydrophobic DES-based dispersive liquid–liquid microextraction coupled with high-performance liquid chromatography (HPLC) was developed for the analysis of neonicotinoid insecticide residues in various samples. A hydrophobic deep eutectic solvent (DES) was synthesized using decanoic acid as a hydrogen bond donor and tetrabutylammonium bromide (TBABr) as a hydrogen bond-acceptor. DESs were synthesized and characterized by Fourier transform-infrared (FTIR) spectroscopy. Two disperser solvents were substituted with surfactants and acetonitrile, which could afford more effective emulsification and make the extraction relatively greener. The hydrophobic DES extraction phase occurred 10 min after centrifugation, being easy to be collected for analysis. Several parameters were investigated and optimized. Under the optimum condition, the calibration curve of this method was linear in the range of 0.003–1.0-µg·mL−1, with a correlation coefficient (R2) higher than 0.99 and a good repeatability, with the relative standard deviations (RSDs) were less than 5.00%. The limits of detection were in the range of 0.001–0.003 µg·mL−1; the limits of quantitation were in the range of 0.003–0.009 µg·mL·mL−1. Finally, the presented method was implemented to determine the neonicotinoid insecticide residues in water, soil, egg yolk samples and acceptable recoveries were obtained.